2016
DOI: 10.1002/dmrr.2787
|View full text |Cite
|
Sign up to set email alerts
|

Circulating fibroblast growth factor‐23 plasma levels predict adverse cardiovascular outcomes in patients with diabetes mellitus with coronary artery disease

Abstract: FGF-23 plasma levels predict adverse cardiovascular outcomes in coronary artery disease patients who have T2D but not in those without T2D. This finding should be confirmed in larger studies. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 38 publications
(48 reference statements)
1
20
1
Order By: Relevance
“…We identified eight circulating biomarkers, including four novel ones, for incident cardiovascular events after adjustment for established risk factors. Our results replicate previous findings in individuals with type 2 diabetes of associations of increased levels of MMP-12 [ 17 ], FGF-23 [ 28 ], TNFR-1 and TNFR-2 [ 29 ] with incident MACE. For the other four biomarkers, we found no previous studies of prospective associations with MACE in type 2 diabetes, although all have been implicated in cardiometabolic disease in other settings.…”
Section: Discussionsupporting
confidence: 91%
“…We identified eight circulating biomarkers, including four novel ones, for incident cardiovascular events after adjustment for established risk factors. Our results replicate previous findings in individuals with type 2 diabetes of associations of increased levels of MMP-12 [ 17 ], FGF-23 [ 28 ], TNFR-1 and TNFR-2 [ 29 ] with incident MACE. For the other four biomarkers, we found no previous studies of prospective associations with MACE in type 2 diabetes, although all have been implicated in cardiometabolic disease in other settings.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, a large community based study also with FGF-23 concentration within normal range followed for 19 years, demonstrated an association between higher FGF-23 and increased risk of incident ESRD independent of kidney function[ 8 ]. In a mixed diabetic and non-diabetic cohort of patients with coronary heart disease, higher FGF-23 predicted CV outcomes in the diabetic but not in the non-diabetic patients suggesting potential biological differences in the FGF-23 response between patients with and without diabetes[ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum FGF23 levels are also markedly elevated in patients with acute decompensated heart failure (ADHF), which is a sudden worsening of the signs and symptoms of heart failure, including difficulty breathing, leg or feet swelling, and fatigue (Andersen et al, 2016 ), with heart failure and a reduced ejection fraction (Koller et al, 2015 ), incident atrial fibrillation (Mathew et al, 2014 ), coronary heart disease, heart failure, and cardiovascular mortality (Lutsey et al, 2014 ), non-ischemic cardiac disease (Imazu et al, 2014 ), chronic systolic heart failure (Wohlfahrt et al, 2015 ), and CAD (Tuñón et al, 2016 ). However, myocardial FGF23 gene expression levels and FGF23 immunostaining are not increased in ADHF patients, suggesting that the myocardium does not contribute to elevated circulating FGF23 levels in ADHF and that FGF23 plays roles in heart failure in an endocrine manner (Andersen et al, 2016 ).…”
Section: Pathophysiological Roles Of Fgfs Indicated By Human Diseasesmentioning
confidence: 99%